Assessing infiltration and exfiltration on the Performance of Urban Sewer Systems (APUSS) - Ellis, J. B. (J. Bryan); Bertrand-Krajewski, J. L. (Jean-Luc); European Commission. Community Research (London [England] : IWA Publishing, 2010)
During the period 2001-2004, the European research project APUSS (Assessing infiltration and exfiltration on the Performance of Urban Sewer Systems) was devoted to sewer infiltration and exfiltration questions. This synthetic final report describes the objectives, methods and main results for each Work Area. During the period 2001-2004, the European research project APUSS (Assessing infiltration and exfiltration on the Performance of Urban Sewer Systems) was devoted to sewer infiltration and exfiltration questions. This synthetic final report describes the objectives, methods and main results for each Work Area.
""Chapter 8: Test and field applications of methods in Italy""""Chapter 9: Test and field applications of methods in the UK""; ""Chapter 10: Modelling sub-catchment approaches to leakage rates""; ""Chapter 11: Generic multi-criteria methodology to compare investment/rehabilitation strategies: principles and case study""; ""Chapter 12: Economic and operational aspects""; ""Chapter 13: APUSS: Perspectives and conclusions""; ""List of publications""
Includes bibliographical references
Keywords: Sewerage -- Maintenance and repair; Seepage